Methyl 5-ferrocenyl-5a-hydroxy-1-methyl-10-oxo-2,3,3a,4,5a,10-hexahydro-1H-indeno[1,2:2′,3′]furo[3′,4′-b]pyrrole-3a-carboxylate - Kamala, E. Theboral Sugi (International Union of Crystallography, 2009)
In the title compound, [Fe(C(5)H(5))(C(21)H(20)NO(5))], the pyrrolidine and cyclopentanone rings exhibit a twist conformation. The pyrrolidine ring is almost perpendicular to the cyclopentanone ring, making a dihedral angle of 81.91 (6)°. The molecular conformation is stabilized by an intramolecular O—H⋯N hydrogen bond and C—H⋯O interactions. The crystal structure is stabilized by intermolecular C—H⋯O interactions.